البلاغة في كتاب "صور من حياة التابعين" للدكتور عبد الرحمن رأفت الباشا: Rhetorical Analysis of Dr. Abdul Rahman Rafat Al-Basha’s Book "Sowar Min Hayat Al-Taabi’een" - Hafiz Azfar Khurshid; Prof. Dr Hafiz Abdul Qadeer; Prof. Dr Hafiz Muhammad Altaf (Al Manhal Research Journal, 2025)
This research paper presents an analysis of the rhetorical merits of Dr. Abdul Rahman Rafat Al-Basha's famous book "Sowar Min Hayat Al-Taabi'een". The main objective of the research is to present a literary analysis of the rhetorical styles—expression, semantics, and embellishment—used in the book, as well as to highlight the author's personality and literary contributions. The research has adopted a narrative and analytical approach, in which excerpts of rhetorical samples have been selected directly from the book and a detailed analysis has been presented. The results of the research showed that Dr. Abdul Rahman Raafat Al-Basha created a literary masterpiece by presenting historical events in a rhetorical style. The book uses figurative devices (simile, metaphor, and metonymy) to create effective imagery, while semantic techniques (declarative and imperative styles, restriction, conjunction and separation, conciseness, elaboration, and equilibrium) have introduced diversity and effectiveness into the discourse. Furthermore, the use of rhetorical embellishments (both verbal and moral) has endowed the prose with the beauty of poetry.